High-strength flame-retardant fabric for aerospace and preparation method thereof
Through the blending of fine denier fiber and wool fiber and the lamination technology of polyammonium phosphate compound castor oil-based polyurethane, the environmental pollution problem of harmful substances in existing aerospace-grade high-strength flame retardant fabrics is solved, and the high strength and flame retardant performance is achieved, which meets the requirements of environmental protection and sustainable development.
Patent Information
- Application Number
- CN202411981563.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
The existing aerospace-grade high-strength flame retardant fabrics contain harmful substances such as halogen, which poses a huge burden on the environment.
Fine denier fiber and wool fiber are blended, and bonded with fabrics through ammonium polyphosphate compound castor oil-based polyurethane film, laminated, dried and cured to form a high-strength flame retardant fabric.
It achieves a balance between high strength and flame retardant performance, while avoiding the pollution of the environment by traditional flame retardants, and meeting modern standards for environmental protection and sustainable development.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the field of fabric preparation, and in particular to a high-strength flame-retardant fabric for aerospace and a preparation method thereof. Background Art
[0002] The aerospace industry has extremely high safety requirements. During flight, any fire inside an aircraft or spacecraft may develop rapidly and cause serious consequences. Therefore, highly efficient flame-retardant fabrics are essential, which can effectively delay the spread of fire, provide passengers and crew with more escape time, and greatly improve the survival rate. At the same time, under extreme conditions, high-strength fabrics can protect the internal structure from damage, ensure structural integrity, and thus extend the service life. Therefore, the development of high-strength flame-retardant fabrics for aerospace is not only a necessary measure to meet safety and regulatory requirements, but the innovation and improvement of such fabrics is an indispensable part of the development of aerospace technology.
[0003] With the global emphasis on environmental protection and sustainable development, aviation materials are also developing towards environmental friendliness. Currently, most of the aerospace-grade high-strength flame-retardant fabrics on the market contain harmful substances such as halogen flame retardants, such as a method for preparing a flame-retardant fabric disclosed in patent number CN118029077A. Therefore, developing a flame-retardant high-strength fabric made of recyclable or bio-based materials not only reduces the burden on the environment, but also meets the expectations of modern consumers. Summary of the invention
[0004] In order to solve the technical problem that the high-strength flame-retardant fabrics mentioned in the above background technology contain harmful substances such as halogen flame retardants, which cause great burden on the environment, the present invention provides an aerospace high-strength flame-retardant fabric and a preparation method, which can not only meet the high-strength and flame-retardant performance requirements, but also take into account the modern standards of environmental protection and sustainable development. The specific technical solution of the present invention is: a preparation method of a high-strength flame-retardant fabric for aerospace, comprising the following steps: 1) Weaving fine denier fiber and wool fiber to obtain basic fabric, adding lining to the basic fabric, and successively performing sewing, curling, desizing, dyeing and pre-forming to obtain pre-formed grey cloth, wherein the fabric tightness of the basic fabric is 75% to 95%; 2) Laminating the prepared ammonium polyphosphate compounded castor oil-based polyurethane film with the fabric, laminating, drying and curing to obtain high-strength flame-retardant fabric for aerospace.
[0005] The invention blends fine denier aramid fiber with superior high strength and natural flame retardancy with wool with natural flame retardancy, which not only enhances the flame retardancy of the fabric, but also improves its comfort and wearing experience, so that the fabric achieves a good balance between protection performance and user comfort; at the same time, castor oil is selected as the basic bio-based polyol source. Castor oil, as a renewable resource, has a unique chemical structure and natural flame retardancy. The rich oleic acid and linoleic acid components in castor oil not only give it good chemical modifiability potential, but also provide an ideal basis for subsequent polymerization and modification; then, castor oil is reacted with glycerol to increase the functionality of the molecular chain; then, by reacting with isocyanate, The cyanate reacts chemically to convert castor oil into castor oil-based polyurethane, which contains a large number of terminal active functional groups. These functional groups can enhance the adhesion and durability of the coating to the base fabric through chemical crosslinking or modification; halogen-free phosphorus-based flame retardant ammonium polyphosphate is selected to avoid the environmental and health risks that may exist in traditional flame retardants; the halogen-free flame retardant ammonium polyphosphate is compounded with castor oil-based polyurethane through chemical bonding to form a coating slurry. This composite method can ensure that the flame retardant is evenly distributed in the polyurethane matrix, thereby maximizing the flame retardant effect of the coating; finally, it is applied to the fabric surface through lamination to form a uniform and continuous protective layer to achieve high-strength flame retardant performance.
[0006] As a preference, 3D weaving technology is selected for weaving to produce fabrics with tight and stable structure, which greatly improves the fabric's resistance to stretching and tearing. The dense structure of 3D weaving helps to form a more uniform and continuous protective layer, effectively preventing the fabric from being damaged under extreme conditions.
[0007] Furthermore, the preparation method of the ammonium polyphosphate composite castor oil-based polyurethane film in step 2) comprises the following steps: S1) heating castor oil, adding glycerol and stannous octoate to obtain castor oil polyol; S2) adding isocyanate and iron-based catalyst to castor oil polyol to obtain castor oil-based polyurethane; S3) adding ammonium polyphosphate to the above-mentioned castor oil-based polyurethane and mixing evenly to obtain slurry; S4) pressing and aging the slurry to obtain the ammonium polyphosphate composite castor oil-based polyurethane film.
[0008] Preferably, the castor oil is castor oil with a low acid value of <0.5 mg KOH / g.
[0009] Preferably, the isocyanate is 4,4'-diphenylmethane diisocyanate.
[0010] Furthermore, the added amount of the iron catalyst is 0.1-0.2% of the total mass of the castor oil polyol and the isocyanate.
[0011] Furthermore, the added amount of stannous octoate is 0.1-0.2% of the total mass of castor oil and glycerol.
[0012] Furthermore, in S3), the amount of ammonium polyphosphate added is 20-25% of the mass of the castor oil-based polyurethane.
[0013] Furthermore, the fine denier fiber has a single filament fiber size of 0.2 to 1.2 deniers.
[0014] Furthermore, the warp yarn density of the base fabric ranges from 100 to 300 yarns / inch; the weft yarn density ranges from 80 to 150 yarns / inch.
[0015] Furthermore, the lining material includes composite polyester, nylon and special cotton cloth, and adopts a multi-layer composite structure, which not only further enhances the overall strength and durability of the fabric, but also maintains the lightweight characteristics of the material, ensuring that the fabric can maintain excellent performance and comfort even in complex environments.
[0016] Furthermore, in the lamination process, the glue coating thickness is 30-35 μm and the speed is 70 m / min.
[0017] Furthermore, a high-strength flame-retardant fabric for aerospace use is prepared according to the above preparation method.
[0018] Compared with the prior art, the beneficial effects of the present invention are: 1) The base fabric of the present invention is blended with fine denier aramid fiber having superior high strength and natural flame retardancy and wool having natural flame retardancy, achieving a good balance between protection performance and user comfort.
[0019] 2) The composite coating slurry used in the present invention is an ammonium polyphosphate compounded with a castor oil-based polyurethane composite coating slurry. The castor oil-based polyurethane is chemically bonded with the halogen-free flame retardant ammonium polyphosphate to form a coating slurry, ensuring that the flame retardant is evenly distributed in the polyurethane matrix, thereby maximizing the flame retardant effect of the coating.
[0020] 3) The coating slurry formed by the castor oil-based polyurethane and the halogen-free flame retardant ammonium polyphosphate complex is applied to the fabric surface by lamination to form a uniform and continuous protective layer to achieve high-strength flame retardant performance. DETAILED DESCRIPTION
[0021] The present invention will be further described below in conjunction with the embodiments.
[0022] Specific examples and comparative examples.
[0023] Example 1 A high-strength flame-retardant fabric for aerospace, the preparation method of which is as follows: 1) Preparation of base fabric Through 3D weaving technology, fine denier aramid fiber with a monofilament fiber density of 0.8 denier is mixed with wool fiber to form a basic fabric with a fabric density of 90%, a warp density of 250 yarns / inch, and a weft density of 120 yarns / inch. Composite polyester, cotton nylon and special cotton cloth are added. An industrial-grade sewing machine is used to sew the edge of the grey cloth by three-thread overlocking. The number of stitches per inch is about 8 stitches, and the seam width is controlled to 5mm. The grey cloth is placed in a hot water bath containing enzyme preparations, the temperature is maintained at 55°C, and the soaking time is 30 minutes until the slurry is completely dissolved. After decomposition, the fabric is thoroughly washed with clean water to remove residual enzymes and decomposition products, and finally the excess water is dried by a centrifugal dehydrator. The desized grey fabric is immersed in a dyeing vat, preheated at 60°C for 10 minutes, and then gradually heated to 95°C. The dyeing is continued for 60 minutes. During this period, constant stirring is required to ensure uniform color distribution. After dyeing, the fabric is rinsed with clean water again, and then fixed and dried. Among them, dyeing device: JW-1832; temperature: 95C; vehicle speed: 80m / min; padding pressure: 0.3MPa; steam pressure: 2.5 kg; The dyed grey cloth is sent to the pre-setting machine, and the set temperature is 210℃, the speed is 100m / min, the padding pressure is 0.25Mpa, and the process operation time is 30s. The oven temperature of the setting machine is 210℃; the speed is 100m / min; the padding pressure is 0.25Mpa; the process operation time is 30s. This step helps to stabilize the fabric size, eliminate internal stress, and improve the feel and flatness.
[0024] 2) Preparation of coating slurry 200 grams of low-acid castor oil is heated to 60°C, 30 grams of glycerol and an appropriate amount of stannous octoate (accounting for 0.15% of the total mass of castor oil and glycerol) are added, and the mixture is stirred and reacted for 2 hours to obtain castor oil polyol; an excess of 4,4'-diphenylmethane diisocyanate (MDI) and an iron-based catalyst (accounting for 0.15% of the total mass of castor oil polyol and MDI) are added to the above solution, and the mixture is continuously stirred and kept at a temperature of 70°C for 4 hours to form castor oil-based polyurethane; ammonium polyphosphate is added according to 22% of the mass of the castor oil-based polyurethane, and the mixture is fully mixed to obtain a coating slurry.
[0025] 3) Lamination process The coating slurry prepared in step 2) is impregnated with a resin solution and dried using a dipping machine, and is adjusted and controlled according to the requirements of coating thickness and coating rate under the conditions of temperature 80°C, time 12min, and press pressure 0.1MPa, pressed and matured into a block, and then the newly formed resin film and fabric are bonded and laminated on a calender. After pressing, it is dried and cured to obtain a high-strength flame-retardant fabric for aerospace, so that a strong chemical bond is formed between the coating and the fabric surface, wherein the glue coating thickness is controlled to be 32μm, the coating viscosity on the machine is 8000cps, and the glue amount is 333g / m 2 , the speed is controlled at 70m / min.
[0026] 4) Performance testing The mechanical strength (breaking capacity) and combustion performance (continuous burning time, ignition time, and damaged length) of the prepared fabrics were tested.
[0027] Comparative Example 1 The difference between this comparative example and Example 1 is that in step 1), the fabric tightness is 60%, and the rest of the process is the same as that of Example 1, and the specific steps are as follows: 1) Preparation of base fabric Through 3D weaving technology, fine denier aramid fiber with a monofilament fiber density of 0.8 denier is mixed with wool fiber to form a basic fabric with a fabric density of 90%, a warp density of 250 yarns / inch, and a weft density of 120 yarns / inch. Composite polyester, cotton nylon and special cotton cloth are added. An industrial-grade sewing machine is used to sew the edge of the grey cloth by three-thread overlocking. The number of stitches per inch is about 8 stitches, and the seam width is controlled to 5mm. The grey cloth is placed in a hot water bath containing enzyme preparations, the temperature is maintained at 55°C, and the soaking time is 30 minutes until the slurry is completely dissolved. After decomposition, the fabric is thoroughly washed with clean water to remove residual enzymes and decomposition products, and finally the excess water is dried by a centrifugal dehydrator. The desized grey fabric is immersed in a dyeing vat, preheated at 60°C for 10 minutes, and then gradually heated to 95°C. The dyeing is continued for 60 minutes. During this period, constant stirring is required to ensure uniform color distribution. After dyeing, the fabric is rinsed with clean water again, and then fixed and dried. Among them, dyeing device: JW-1832; temperature: 95C; vehicle speed: 80m / min; padding pressure: 0.3MPa; steam pressure: 2.5 kg; The dyed grey cloth is sent to the pre-setting machine, and the set temperature is 210℃, the speed is 100m / min, the padding pressure is 0.25Mpa, and the process operation time is 30s. The oven temperature of the setting machine is 210 degrees; the speed is 100m / min; the padding pressure is 0.25Mpa; the process operation time is 30s. This step helps to stabilize the fabric size, eliminate internal stress, and improve the feel and flatness.
[0028] 2) Preparation of coating slurry 200 grams of low-acid castor oil is heated to 60°C, 30 grams of glycerol and an appropriate amount of stannous octoate (accounting for 0.15% of the total mass of castor oil and glycerol) are added, and the mixture is stirred and reacted for 2 hours to obtain castor oil polyol; an excess of 4,4'-diphenylmethane diisocyanate (MDI) and an iron-based catalyst (accounting for 0.15% of the total mass of castor oil polyol and MDI) are added to the above solution, and the mixture is continuously stirred and kept at a temperature of 70°C for 4 hours to form castor oil-based polyurethane; ammonium polyphosphate is added according to 22% of the mass of the castor oil-based polyurethane, and the mixture is fully mixed to obtain a coating slurry.
[0029] 3) Lamination process The coating slurry prepared in step 2) is impregnated with a resin solution and dried using a dipping machine, and is adjusted and controlled according to the requirements of coating thickness and coating rate under the conditions of temperature 80°C, time 12min, and press pressure 0.1MPa, pressed and matured into a block, and then the newly formed resin film and fabric are bonded and laminated on a calender. After pressing, it is dried and cured to obtain a high-strength flame-retardant fabric for aerospace, so that a strong chemical bond is formed between the coating and the fabric surface, wherein the glue coating thickness is controlled to be 32μm, the coating viscosity on the machine is 8000cps, and the glue amount is 333g / m 2 , the speed is controlled at 70m / min.
[0030] 4) Performance testing The mechanical strength (breaking capacity) and combustion performance (continuous burning time, ignition time, and damaged length) of the prepared fabrics were tested.
[0031] Through 3D weaving technology, fine denier aramid fiber with a monofilament fiber density of 0.8 denier is mixed with wool fiber to form a basic fabric with a fabric density of 60%, a warp density of 250 yarns / inch, and a weft density of 120 yarns / inch. Composite polyester, cotton nylon and special cotton cloth are added. An industrial-grade sewing machine is used to sew the edge of the grey cloth by three-thread overlocking. The number of stitches per inch is about 8 stitches, and the seam width is controlled to 5mm. The grey cloth is placed in a hot water bath containing enzyme preparations, the temperature is maintained at 55°C, and the soaking time is 30 minutes until the slurry is completely dissolved. After decomposition, the fabric is thoroughly washed with clean water to remove residual enzymes and decomposition products, and finally the excess water is dried by a centrifugal dehydrator. The desized grey fabric is immersed in a dyeing vat, preheated at 60°C for 10 minutes, and then gradually heated to 95°C. The dyeing is continued for 60 minutes. During this period, constant stirring is required to ensure uniform color distribution. After dyeing, the fabric is rinsed with clean water again, and then fixed and dried. Among them, dyeing device: JW-1832; temperature: 95C; vehicle speed: 80m / min; padding pressure: 0.3MPa; steam pressure: 2.5 kg; The dyed grey cloth is sent to the pre-setting machine, and the set temperature is 210℃, the speed is 100m / min, the padding pressure is 0.25Mpa, and the process operation time is 30s. The oven temperature of the setting machine is 210℃; the speed is 100m / min; the padding pressure is 0.25Mpa; the process operation time is 30s. This step helps to stabilize the fabric size, eliminate internal stress, and improve the feel and flatness.
[0032] 2) Preparation of coating slurry 200 grams of low-acid castor oil is heated to 60°C, 30 grams of glycerol and an appropriate amount of stannous octoate (accounting for 0.15% of the total mass of castor oil and glycerol) are added, and the mixture is stirred and reacted for 2 hours to obtain castor oil polyol; an excess of 4,4'-diphenylmethane diisocyanate (MDI) and an iron-based catalyst (accounting for 0.15% of the total mass of castor oil polyol and MDI) are added to the above solution, and the mixture is continuously stirred and kept at a temperature of 70°C for 4 hours to form castor oil-based polyurethane; ammonium polyphosphate is added according to 22% of the mass of the castor oil-based polyurethane, and the mixture is fully mixed to obtain a coating slurry.
[0033] 3) Lamination process The coating slurry prepared in step 2) is impregnated with a resin solution and dried using a dipping machine, and is adjusted and controlled according to the requirements of coating thickness and coating rate under the conditions of temperature 80°C, time 12min, and press pressure 0.1MPa, pressed and matured into a block, and then the newly formed resin film and fabric are bonded and laminated on a calender. After pressing, it is dried and cured to obtain a high-strength flame-retardant fabric for aerospace, so that a strong chemical bond is formed between the coating and the fabric surface, wherein the glue coating thickness is controlled to be 32μm, the coating viscosity on the machine is 8000cps, and the glue amount is 333g / m 2 , the speed is controlled at 70m / min.
[0034] 4) Performance testing The mechanical strength (breaking capacity) and combustion performance (continuous burning time, ignition time, and damaged length) of the prepared fabrics were tested.
[0035] Table 1 Effect of fabric tightness on the mechanical properties of the final fabric From the data in Table 1, it can be concluded that weaving a fabric with a tight and stable structure can greatly improve the fabric's tensile and tear resistance, help form a more uniform and continuous protective layer, and effectively prevent the fabric from being damaged under extreme conditions.
[0036] Comparative Example 2 The difference between this comparative example and Example 1 is that in this comparative example, step 1) uses only fine denier aramid fiber with a monofilament fiber size of 0.8 denier, and does not use wool fiber. The specific steps are: Through 3D weaving technology, fine denier aramid fiber with a monofilament fiber density of 0.8 denier is woven into a basic fabric with a fabric density of 90%, a warp density of 250 yarns / inch, and a weft density of 120 yarns / inch. Composite polyester, nylon and special cotton cloth are added. An industrial-grade sewing machine is used to sew the edge of the grey cloth by three-thread overlocking. The number of stitches per inch is about 8 stitches, and the seam width is controlled to be 5mm. The grey cloth is placed in a hot water bath containing enzyme preparations, the temperature is maintained at 55°C, and the soaking time is 30 minutes until the slurry is completely dissolved. , thoroughly wash the fabric with clean water to remove residual enzymes and decomposition products, and finally use a centrifugal dehydrator to spin off excess water, immerse the desized grey fabric in a dyeing vat, preheat at 60°C for 10 minutes, and then gradually heat up to 95°C, and continue dyeing for 60 minutes. During this period, continuous stirring is required to ensure uniform color distribution. After dyeing, rinse the fabric with clean water again, then perform color fixing treatment, and finally spin off the water. Among them, dyeing device: JW-1832; temperature: 95C; vehicle speed: 80m / min; padding pressure: 0.3MPa; steam pressure: 2.5 kg; The dyed grey cloth is sent to the pre-setting machine, and the set temperature is 210℃, the speed is 100m / min, the padding pressure is 0.25Mpa, and the process operation time is 30s. The oven temperature of the setting machine is 210℃; the speed is 100m / min; the padding pressure is 0.25Mpa; the process operation time is 30s. This step helps to stabilize the fabric size, eliminate internal stress, and improve the feel and flatness.
[0037] 2) Preparation of coating slurry 200 grams of low-acid castor oil is heated to 60°C, 30 grams of glycerol and an appropriate amount of stannous octoate (accounting for 0.15% of the total mass of castor oil and glycerol) are added, and the mixture is stirred and reacted for 2 hours to obtain castor oil polyol; an excess of 4,4'-diphenylmethane diisocyanate (MDI) and an iron-based catalyst (accounting for 0.15% of the total mass of castor oil polyol and MDI) are added to the above solution, and the mixture is continuously stirred and kept at a temperature of 70°C for 4 hours to form castor oil-based polyurethane; ammonium polyphosphate is added according to 22% of the mass of the castor oil-based polyurethane, and the mixture is fully mixed to obtain a coating slurry.
[0038] 3) Lamination process The coating slurry prepared in step 2) is impregnated with a resin solution and dried using a dipping machine, and pressed and aged into a block at a temperature of 80°C, a time of 12 minutes, and a press pressure of 0.1 MPa. Then, the newly formed resin film and the fabric are bonded and laminated on a calender. After pressing, they are dried and cured to obtain a high-strength flame-retardant fabric for aerospace, so that a strong chemical bond is formed between the coating and the fabric surface, wherein the glue coating thickness is controlled to be 32 μm, the coating viscosity on the machine is 8000 cps, and the glue amount is 333 g / m 2 , the speed is controlled at 70m / min.
[0039] 4) Performance testing The mechanical strength (breaking capacity) and combustion performance (continuous burning time, ignition time, and damaged length) of the prepared fabrics were tested.
[0040] Comparative Example 3 The difference between this comparative example and Example 1 is that in this comparative example, step 1) only uses wool fiber and does not use fine denier aramid fiber for blending. The specific steps are: Through 3D weaving technology, fine denier aramid fiber with a monofilament fiber density of 0.8 denier is mixed with wool fiber to form a basic fabric with a fabric density of 90%, a warp density of 250 yarns / inch, and a weft density of 120 yarns / inch. Composite polyester, cotton nylon and special cotton cloth are added. An industrial-grade sewing machine is used to sew the edge of the grey cloth by three-thread overlocking. The number of stitches per inch is about 8 stitches, and the seam width is controlled to 5mm. The grey cloth is placed in a hot water bath containing enzyme preparations, the temperature is maintained at 55°C, and the soaking time is 30 minutes until the slurry is completely dissolved. After decomposition, the fabric is thoroughly washed with clean water to remove residual enzymes and decomposition products, and finally the excess water is dried by a centrifugal dehydrator. The desized grey fabric is immersed in a dyeing vat, preheated at 60°C for 10 minutes, and then gradually heated to 95°C. The dyeing is continued for 60 minutes. During this period, constant stirring is required to ensure uniform color distribution. After dyeing, the fabric is rinsed with clean water again, and then fixed and dried. Among them, dyeing device: JW-1832; temperature: 95C; vehicle speed: 80m / min; padding pressure: 0.3MPa; steam pressure: 2.5 kg; The dyed grey cloth is sent to the pre-setting machine, and the set temperature is 210℃, the speed is 100m / min, the padding pressure is 0.25Mpa, and the process operation time is 30s. The oven temperature of the setting machine is 210 degrees; the speed is 100m / min; the padding pressure is 0.25Mpa; the process operation time is 30s. This step helps to stabilize the fabric size, eliminate internal stress, and improve the feel and flatness.
[0041] 2) Preparation of coating slurry 200 grams of low-acid castor oil was heated to 60°C, 30 grams of glycerol and stannous octoate (accounting for 0.15% of the total mass of castor oil and glycerol) were added, and the mixture was stirred and reacted for 2 hours to obtain castor oil polyol; an excess of 4,4'-diphenylmethane diisocyanate (MDI) and an iron-based catalyst (accounting for 0.15% of the total mass of castor oil polyol and MDI) were added to the above solution, and the mixture was continuously stirred and kept at 70°C for 4 hours to form castor oil-based polyurethane; ammonium polyphosphate was added according to 22% of the mass of castor oil-based polyurethane, and the mixture was fully mixed to obtain a coating slurry.
[0042] 3) Lamination process The coating slurry prepared in step 2) is impregnated with a resin solution and dried using a dipping machine, and is adjusted and controlled according to the requirements of coating thickness and coating rate under the conditions of temperature 80°C, time 12min, and press pressure 0.1MPa, pressed and matured into a block, and then the newly formed resin film and fabric are bonded and laminated on a calender. After pressing, it is dried and cured to obtain a high-strength flame-retardant fabric for aerospace, so that a strong chemical bond is formed between the coating and the fabric surface, wherein the glue coating thickness is controlled to be 32μm, the coating viscosity on the machine is 8000cps, and the glue amount is 333g / m 2 , the speed is controlled at 70m / min.
[0043] 4) Performance testing The mechanical strength (breaking capacity) and combustion performance (continuous burning time, ignition time, and damaged length) of the prepared fabrics were tested.
[0044] Table 2 Effect of fiber blending on fabric properties From the data in Table 2, it can be concluded that fine denier aramid fiber, as the main material, has superior high strength and natural flame retardancy. Adding wool fiber for blending and utilizing the natural flame retardant properties and excellent comfort of wool, the blending of the two can effectively enhance the flame retardant effect of the fabric, and also improve its comfort and wearing experience, so that the fabric achieves a good balance between protective performance and user comfort.
[0045] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0046] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing high-strength flame-retardant fabric for aerospace, characterized in that: The following steps are involved: 1) Weaving fine denier fiber and wool fiber to obtain basic fabric, adding lining to the basic fabric, and successively sewing, curling, desizing, dyeing and pre-forming to obtain pre-formed grey cloth, wherein the fabric tightness of the basic fabric is 75%~95%; 2) The prepared ammonium polyphosphate compounded castor oil-based polyurethane film is bonded to the fabric, and after lamination, drying and curing, a high-strength flame-retardant fabric for aerospace is obtained.
2. The method for preparing a high-strength flame-retardant fabric for aerospace according to claim 1, characterized in that: The method for preparing the ammonium polyphosphate-castor oil-based polyurethane film in step 2) comprises the following steps: S1) heating castor oil, adding glycerol and stannous octoate to obtain castor oil polyol; S2) adding isocyanate and an iron-based catalyst to castor oil polyol to obtain castor oil-based polyurethane; S3) adding ammonium polyphosphate to the castor oil-based polyurethane and mixing them evenly to obtain a slurry; S4) The slurry is pressed and aged to obtain an ammonium polyphosphate-compounded castor oil-based polyurethane film.
3. The method for preparing a high-strength flame-retardant fabric for aerospace according to claim 2, characterized in that: The amount of the iron catalyst added is 0.1-0.2% of the total mass of castor oil polyol and isocyanate.
4. The method for preparing a high-strength flame-retardant fabric for aerospace according to claim 2 or 3, characterized in that: The added amount of stannous octoate is 0.1-0.2% of the total mass of castor oil and glycerol.
5. The method for preparing a high-strength flame-retardant fabric for aerospace according to claim 2, characterized in that: In S3), the amount of ammonium polyphosphate added is 20-25% of the mass of castor oil-based polyurethane.
6. The method for preparing a high-strength flame-retardant fabric for aerospace according to claim 1, characterized in that: The single-filament fiber density of fine denier fiber is 0.2~1.2 denier.
7. The method for preparing a high-strength flame-retardant fabric for aerospace according to claim 1 or 6, characterized in that: The warp yarn density of the basic fabric ranges from 100 to 300 yarns / inch; the weft yarn density ranges from 80 to 150 yarns / inch.
8. The method for preparing a high-strength flame-retardant fabric for aerospace according to claim 1, characterized in that: The lining material includes composite polyester, nylon and special cotton cloth.
9. The method for preparing a high-strength flame-retardant fabric for aerospace according to claim 1, characterized in that: In the lamination process, the glue coating thickness is 30~35μm and the speed is 70m / min.
10. A high-strength flame-retardant fabric for aerospace use prepared according to the preparation method of any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of castor oil based flame-retardant PIPA polyol film
CN103360565A
Flame-retardant fabric
CN104480617A
Fire retardant paint and preparation method thereof
CN104893551A
PU (polyurethane) spray coating for mines and preparation method of coating
CN104893556A
Thermal-protection knitted fabric
CN108327362A